2006
DOI: 10.1097/01.tp.0000198122.15235.a7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Portal Venous Circulation for Liver Graft Function after Living-Donor Liver Transplantation

Abstract: Liver graft function was better when PVF and graft compliance were higher and PVP was maintained under 20 mmHg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 22 publications
7
82
0
1
Order By: Relevance
“…Detailed surgical procedures for intentional modulation of PVP have been described elsewhere [40,41] . Paradoxically, the acceptable minimum GRWR of < 0.7 is possible at graft selection [40] because intentional PVP modulation during LDLT will prevent small-for-size syndrome after LDLT [38][39][40][41][42] . Although intentional PVP control seems to overcome an GRWR of < 0.7, these grafts still cause critical problems when evaluated retrospectively [40] .…”
Section: Intentional Modulation Of Pvp During Ldltmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed surgical procedures for intentional modulation of PVP have been described elsewhere [40,41] . Paradoxically, the acceptable minimum GRWR of < 0.7 is possible at graft selection [40] because intentional PVP modulation during LDLT will prevent small-for-size syndrome after LDLT [38][39][40][41][42] . Although intentional PVP control seems to overcome an GRWR of < 0.7, these grafts still cause critical problems when evaluated retrospectively [40] .…”
Section: Intentional Modulation Of Pvp During Ldltmentioning
confidence: 99%
“…ICG kinetics reflect the functional hepatocytes (cell volume) and effective PVF (clearance) [31,[49][50][51][52] , and PVF is a major determinant of kICG in the normal liver [32,34,49,51,53] . The PVF has a large influence on liver regeneration after LT [32,43] , and reversible damage to hepatocytes begins immediately after graft recirculation [32,38,39,43] . Some researchers have focused on ICG kinetics as a liver function test after LT [31,32] , and kICG values can predict clinical outcomes in the early postoperative period after LDLT by closely reflecting the influence of systemic dynamics on the splanchnic circulation [32] .…”
Section: Strategic Value Of Icg Kinetics During Ltmentioning
confidence: 99%
See 1 more Smart Citation
“…T herefore, indications for concomitant splenectomy should be decided carefully. Although we perform splenectomy concurrently with LDLT to modulate portal venous pressure, especially when the portal venous pressure is over 20 mmHg after reflowing [15] , we do not perform concomitant splenectomy for introduction of IFN therapy routinely at present. Sohara et al [11] have reported the efficacy of PSE on overcoming IFN-related thrombocytopenia after liver transplantation.…”
Section: Recurrent Hepatitis T/momentioning
confidence: 99%
“…However, there is little information about the outcome of LDLT with prior spontaneous portasystemic shunts. It has been generally accepted that adequate PVF is essential for postoperative hepatic regeneration after hepatectomy and partial liver transplantation [18][19][20]. Preserved portasystemic shunt is reported to cause excessive decrease in graft PVF, leading…”
Section: Introductionmentioning
confidence: 99%